Persepsi Pelaku Usaha Terhadap Kewajiban Registrasi Pangan Segar Asal Tumbuhan (Beras) di Kabupaten Tuban - Hariyati, Teti; Soedarto, Teguh; Hendrarini, Hamidah (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Registration of Fresh Food of Plant Origin in Domestic Production of Small Businesses (PSAT-PDUK) to maintain food safety of rice products that will be sold by business actors to the community of Tuban Regency because the issue of food safety is an important issue as the main prerequisite that must be met because it will greatly affect the acceptance of a PSAT product in the market including rice. The total sample in this study was 30 respondents for business actors, 5 respondents for consumers and 10 key informant respondents. Data analysis used in this study was perception analysis using a Likert scale tool and SWOT analysis. The perception of business actors regarding the obligation to register PSAT in Tuban Regency is included in the very good category indicating that they support and feel benefited by the obligation to register PSAT. Efforts to Improve Business Actors Regarding the Obligation to Register Fresh Food of Plant Origin (Rice) in Tuban Regency, namely Utilizing easy registration procedures and government subsidies to increase the participation of business actors and expand the certified rice market and Increase certified rice products with clear information regarding food safety standards, and utilize new market access such as e-commerce and supermarkets.